LINGUOCULTURAL CHARACTERISTICS OF OCCASIONAL WORDS IN ENGLISH AND UZBEK (Scientific journal of the Fergana State University, 2025)
This article explores the linguocultural features of occasional words in Uzbek and English. Occasional words, as individual-stylistic neologisms, are created in literary works to reflect the author’s emotions, enhance stylistic nuances, and suit the context. The study analyzes occasional words formed through affixation and compound structures. It emphasizes that in both languages, occasional words exhibit high emotional and expressive meaning dependent on their context.